PERBANDINGAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH KONFLIK PALESTINA-ISRAEL PADA PERUSAHAAN MITRA ADIPERKASA TBK (MAPI) PERIODE 2023 - Salsabila Khoirunnisa Al Kaafi; Bintis Ti’anatud Diniati; Noventia Ramadhani Putri; Sholikhatun Nisa Nur Janah; Devina Luthvia Putri (JSE: Jurnal Sharia Economica, 2025)
This study aims to determine the differences in stock prices and trading volume of PT Mitra Adiperkasa Tbk (MAPI) shares before and after the Palestine–Israel conflict in 2023. The study uses a quantitative method with a comparative approach and secondary data obtained from Yahoo Finance in the form of closing stock prices and stock trading volume for 30 days before and 30 days after the conflict. Data analysis techniques used include descriptive statistical tests, the Kolmogorov-Smirnov normality test, paired sample t-test, and the Wilcoxon Signed Rank Test. The results show that there is no significant difference in the stock price or trading volume of PT Mitra Adiperkasa Tbk (MAPI) shares before and after the Palestine–Israel conflict, with significance values ​​of 0.841 and 0.931, respectively. This indicates that the Palestine–Israel conflict has not had a significant impact on market reactions to PT Mitra Adiperkasa Tbk (MAPI) shares, because investors tend to consider the company's fundamental conditions and business prospects more than international geopolitical issues in making investment decisions.